5‐HT2CR antagonist/5‐HT2CR inverse agonist recovered the increased isolation‐induced aggressive behavior of BALB/c mice mediated by ADAR1 (p110) expression and Htr2c RNA editing. Issue 3 (7th February 2018) - Yu, Weizhi; Xu, Hong; Xue, Ying; An, Dong; Li, Huairui; Chen, Wei; Yu, Deqin; Sun, Yiping; Ma, Jianmei; Tang, Yiyuan; Xiao, Zhaoyang; Yin, Shengming
Abstract: Introduction: Social isolation enhances the aggressive behavior of animals, but the detailed mechanism remains unclear. Epigenetic studies have suggested that Htr2c RNA editing is closely related to aggressive behavior. This study aims to obtain a fundamental understanding of how social isolation impacts adenosine deaminase acting on RNA 1 (ADAR1, RNA editing enzyme) and Htr2c RNA editing, leading to aggressive behavior, and explore the effective solutions for the recovery of this behavior. Methods: We evaluated 21‐day‐old BALB/c mice with and without isolation for aggressive behavior using a resident‐intruder test. Immune‐reactivity and protein expression of ADAR1 (p110) were measured using immunohistochemistry and Western blotting. Htr2c RNA editing was evaluated using pyrosequencing. In addition, the 5‐HT2C R antagonist SB243213/5‐HT2C R inverse agonist SB206553 was used to treat the isolated mice, and the performance of both treatments on the behavior, ADAR1 (p110) expression, and Htr2c RNA editing in isolated mice was examined. Results: Both the protein expression and immune‐reactivity of ADAR1 (p110) in the amygdala decreased, but the percentage of Htr2c RNA editing at A and B sites of amygdala only showed a moderate increase in isolated BALB/c mice with enhanced aggressive behavior compared to the age‐matched group‐housed BALB/c mice. Additionally, treatment with the 5‐HT2C R antagonist SB243213/5‐HT2C R inverse agonist SB206553 recovered the enhanced aggressive behavior of isolated mice and returned the protein expression and immune‐reactivity of ADAR1 (p110) back to the normal level. Moreover, compared to the age‐matched isolated mice treated with physiological saline, isolated mice treated with 5‐HT2C R inverse agonist SB206553 showed a lower percentage of Htr2c RNA editing at both A and B sites, and the same result occurred in isolated mice treated with 5‐HT2C R antagonist SB243213 at B site of Htr2c RNA editing. Conclusions: The 5‐HT2C R antagonist SB243213/5‐HT2C R inverse agonist SB206553 recovered increased aggressive behavior of isolated BALB/c mice mediated by ADAR1 (p110) expression and Htr2c RNA editing. Abstract : 5‐HT2CR antagonist/5‐HT2CR inverse agonist recovered the increased isolation‐induced aggressive behavior of BALB/c mice mediated by ADAR1 (p110) expression and Htr2c RNA editing.